Roles of Micro Ribonucleic Acids in Astrocytes After Cerebral Stroke - Zhang, Yuansheng; Lei, Li; Zhou, Hu; Lu, Xiaoyang; Cai, Feifei; Li, Tao (Frontiers in Cellular Neuroscience, 2022)
Cerebral stroke is one of the highest-ranking causes of death and the leading cause of disability globally, particularly with an increasing incidence and prevalence in developing countries. Steadily more evidence has indicated that micro ribonucleic acids (miRNAs) have important regulatory functions in gene transcription and translation in the course of cerebral stroke. It is beyond arduous to understand the pathophysiology of cerebral stroke, due in part to the perplexity of influencing the network of the inflammatory response, brain edema, autophagy and neuronal apoptosis. The recent research shows miRNA plays a key role in regulating aquaporin 4, and many essential pathological processes after cerebral stroke. This article reviews the recent knowledge on how miRNA influences the inflammatory response, brain edema, infarction size, and neuronal injury after cerebral stroke. In addition, some miRNAs may serve as potential biomarkers in stroke diagnosis and therapy since the expression of some miRNAs in the blood is stable after cerebral stroke.